Apathetic patients with neurocognitive disorders are more fatigued and fatigable - Daumas, Lyne; Zory, Raphaël; Robert, Philippe; Manera, Valeria (Aging clinical and experimental research, 2022)
Background Apathy is common in neurocognitive disorders (NCD) and manifests as reduced goal-directed behaviors and activities. A decrease in everyday activities can also be due to fatigue, another common symptom in NCD. The aim of this study was to investigate if apathetic patients with NCD are more fatigued and more fatigable. Method A self-report questionnaire and clinical functional tests assessed fatigue and fatigability in 30 apathetic vs 26 non-apathetic NCD participants. The Fatigue Severity Scale (FSS) was administered and a 15-s sustained maximal handgrip contraction and a 6-min walk test (6MWT) were performed. Results Apathetic subjects had higher FSS scores. A decrease in performance was observed in apathetic participants during the sustained maximal handgrip contraction but not the 6MWT. Conclusion Higher self-reported fatigue and greater fatigability during the sustained maximal handgrip contraction test in apathetic subjects suggest the importance of assessing these symptoms in apathetic subjects to properly guide treatment. Clinical trial registration NCT04573712.